On the (im)possible validation of hydrogeological models - Andréassian, Vazken (Comptes Rendus. Géoscience)
This paper revisits the controversy on the validation of hydrogeological models, 30 years after it broke out with the publications by [Konikow and Bredehoeft, 1992a] and [de Marsily et al., 1992]. In that debate, [Konikow and Bredehoeft, 1992a] argued that the word “valid” was misleading to the public and should not be used with respect to models. [de Marsily et al., 1992] answered that while the bases of hydrogeological models (conservation of mass and Darcy’s law) were uncontestable and unconditionally valid, specific validation exercises were dearly needed to evaluate the parameters and the geometry of these models (confronting the models with data they had not seen during the calibration phase). By updating and extending the literature review, we reanalyze this debate and the arguments presented and conclude by proposing an extension of de Marsily’s position, which underlines the necessity to look at validation from two distinct viewpoints, i.e. the point of view of the model’s explanatory power (theoretical content) and the point of view of its predictive power. The explanatory and predictive dimensions of model validation are to be considered separately.